Cardiac Energy Metabolism and Oxidative Stress Biomarkers in Diabetic Rat Treated with Resveratrol - Santos, Klinsmann Carolo dos [UNESP]; Braga, Camila Pereira [UNESP]; Barbanera, Pedro Octavio [UNESP]; Ferreira Seiva, Fabio Rodrigues; Fernandes Junior, Ary [UNESP]; Henrique Fernandes, Ana Angelica [UNESP] (Public Library Science, 2014)
Resveratrol (RSV), polyphenol from grape, was studied to evaluate its effects on calorimetric parameters, energy metabolism, and antioxidants in the myocardium of diabetic rats. The animals were randomly divided into four groups (n = 8): C (control group): normal rats; C-RSV: normal rats receiving RSV; DM: diabetic rats; and DM-RSV: diabetics rats receiving RSV. Type 1 diabetes mellitus was induced with administration of streptozotocin (STZ; 60 mg(-1) body weight, single dose, i.p.). After 48 hours of STZ administration, the animals received RSV (1.0 mg/kg/day) for gavage for 30 days. Food, water, and energy intake were higher in the DM group, while administration of RSV caused decreases (p<0.05) in these parameters. The glycemia decreased and higher final body weight increased in DM-RSV when compared with the DM group. The diabetic rats showed higher serum-free fatty acid, which was normalized with RSV. Oxygen consumption (VO2) and carbon dioxide production (VCO2) decreased (p<0.05) in the DM group. This was accompanied by reductions in RQ. The C-RSV group showed higher VO2 and VCO2 values. Pyruvate dehydrogenase activity was lower in the DM group and normalizes with RSV. The DM group exhibited higher myocardial beta-hydroxyacyl coenzyme-A dehydrogenase and citrate synthase activity, and RSV decreased the activity of these enzymes. The DM group had higher cardiac lactate dehydrogenase compared to the DM-RSV group. Myocardial protein carbonyl was increased in the DM group. RSV increased reduced glutathione in the cardiac tissue of diabetic animals. The glutathione reductase activity was higher in the DM-RSV group compared to the DM group. In conclusion, diabetes is accompanied by cardiac energy metabolism dysfunction and change in the biomarkers of oxidative stress. The cardioprotective effect may be mediated through RVS's ability to normalize free fatty acid oxidation, enhance utilization glucose, and control the biomarkers' level of oxidative stress under diabetic conditions.